2017
DOI: 10.5812/jjcdc.57685
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mental Experience of Patients Suffering From Cancer

Abstract: Background: Despite the remarkable development of medical sciences, cancer has yet remained one of the most important diseases of the current century and the second cause of death following cardiovascular diseases. Although we witnessed considerable development in treating cancer and increased number of survivors, cancer is a unique disease that makes the patients deeply feel helplessness and fear. Methods: A qualitative content analysis research was done. The present study investigated patients' experience an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The results indicated that emotion regulation training, with a positive thinking approach, improved the quality of life and its dimensions among children with cancer in the posttest and follow-up (Tables 4). This finding is somehow in line with results of other studies (16,(28)(29)(30)(31)(32)(33)(34)(35)(36). Ciuluvica, Amerio, and Fulcheri (21) demonstrated that emotion regulation training promoted quality of life among patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results indicated that emotion regulation training, with a positive thinking approach, improved the quality of life and its dimensions among children with cancer in the posttest and follow-up (Tables 4). This finding is somehow in line with results of other studies (16,(28)(29)(30)(31)(32)(33)(34)(35)(36). Ciuluvica, Amerio, and Fulcheri (21) demonstrated that emotion regulation training promoted quality of life among patients.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, cognitive-behavioral therapy enables people to maintain their ideal selves in a constant form and constantly improves their actual selves during a treatment (36). To explain these findings (16,(28)(29)(30)(31)(32)(33)(34)(35), it can be noted that emotion regulation plays a key role in adapting to cancer and being aware of emotions aids children with cancer to improve their mental health. Accordingly, by applying emotion regulation strategies, patients with cancer can deal with their issues and respond adaptively to them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcending both these themes was a search for stability and certainty as participants described managing the challenges posed by their treatment. Feelings of uncertainty have been commonly reported in previous research exploring the experiences of those with cancer (Abdollahzadeh, Moudi, & Khanjani, 2017; Connerty & Knott, 2013; Landmark & Wahl, 2002; Shaha, Cox, Talman, & Kelly, 2008). The results from the present study indicate that participants tried to manage their uncertainty primarily through a desire for normality and the development of a new routine which incorporated the disruption created by treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Breast cancer is the second most common cause of cancer death. [ 1 ] This disease changes the course of a person's life and causes him/her many problems in all physical, mental, social, economic, and family dimensions. Depression, frustration, anger, and sometimes suicidal ideation are common in these patients.…”
Section: Introductionmentioning
confidence: 99%